Experimental investigation and modelling of the curing behaviour of photopolymers. (March 2020) - Rehbein, T.; Lion, A.; Johlitz, M.; Constantinescu, A.
Abstract: This paper focuses on the experimental investigation and modelling of the crosslinking reaction of photopolymers used in additive manufacturing processes such as digital light processing and stereolithography. Starting with general mathematical concepts for the description of the material behaviour of polymeric materials, the importance of modelling the crosslinking reaction is emphasised. In order to characterise the crosslinking reaction experimentally, photocalorimetric measurements with varying isothermal temperature and light intensity are shown. From the exothermic heat flows measured during the crosslinking reaction, the degree of cure can be determined for each experimental scenario as a function of time. It is shown that the test temperature and light intensity have a significant influence on the crosslinking reaction. A modelling approach for the description of the crosslinking reaction incorporating temperature and light intensity is presented. Moreover, parameter identification and a comparison of the proposed model with the experiments are conducted. The identified model has an excellent match with experimental data, resulting in a least square error smaller than 3 %. The proposed model and identification method opens up several extensions for the modelling of the material behaviour. Highlights: Photo-DSC is used to investigate the curing behaviour of a commercial photopolymer. Temperature and light intensity are the main variables for the curing. A differential equation is presented for the degree of cure. Parameter identification is conducted for the proposed model. The model shows a good agreement with the experimental results.